Tempo and Mode: Evidence on a Protracted Split From a Dense Fossil Record - Kimura, Yuri; Flynn, Lawrence J.; Jacobs, Louis L. (Frontiers in Ecology and Evolution, 2021)
Fossil records generally inform paleobiologists about extinct taxa and rates of evolution measured at the scale of millions of years. Good records that are densely sampled through time can reveal species level details such as longevity in local sections. Yet fossil data normally do not address details of lineage microevolution because the density through time of lineage sampling is insufficient to perceive patterns at a precision finer than 106 years in most cases. This study concerns details of a splitting event in the evolution of murine rodents, an event for which multiple fossil samples dated to a precision of 105 years fortuitously document the tempo and mode of origin of sister species, the stems of two extant tribes of mice. Evolution of early Murinae in the northern part of the biogeographically restricted Indian subcontinent between 11.6 and 10.5 Ma involved cladogenesis of two crown taxa, the extant tribes Murini and Arvicanthini. Large samples of fossil rodent teeth document their divergence from a common morphological pool. Definitive basal Murini and Arvicanthini at 10.5 Ma are similar in size and differ by subtle features of the dentition. Those features occur sporadically in the common pool of older fossil teeth at 11.2, 11.4, and 11.6 Ma as inconsistent polymorphisms. Interpreted as a single lineage in the 11.6 to 11.2 Ma interval, variability of this abundant murine incorporated the roots of the two crown tribes. The pattern through time suggests morphological stasis for several hundred thousand years prior to splitting. This special case informs us on one example of evolution and shows that the tempo of splitting evolution in some cases may be measured in hundreds of thousands of years, followed by stasis once daughter species have differentiated morphologically.